2017
DOI: 10.1530/jme-16-0218
|View full text |Cite
|
Sign up to set email alerts
|

Zanthoxylum alkylamides ameliorate protein metabolism disorder in STZ-induced diabetic rats

Abstract: This study aimed to evaluate the protein metabolism effect of Zanthoxylum alkylamides and to explore the potential mechanism in streptozotocin (STZ)-induced diabetic rats. Diabetic rats were orally treated with 2, 4 and 8 mg per kg bw of alkylamides daily for 28 days. Alkylamides decreased the relative weight of the liver and food intake, significantly increased the relative skeletal muscle weight and significantly decreased the blood urea nitrogen levels. Insulin, insulin-like growth factor 1, total protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…As a global disease, DM not only is characterized by elevated blood glucose and blood lipid levels but also displays a protein metabolic disorder, which is primarily caused by the absolute or relative deficiency in insulin secretion [98]. Insulin can promote protein synthesis and inhibit protein decomposition [99], and increased insulin and insulin-like growth factor 1 (IGF1) levels in the serum can improve the protein metabolism (Figure 1). Compared with that in a normal group, protein catabolism in diabetic models was significantly ameliorated, while protein synthesis and the mRNA expression of the IR, IGF1, and IGF1 receptor (IGF1R) were markedly decreased [100].…”
Section: Protein Changes In Ad and Dmmentioning
confidence: 99%
“…As a global disease, DM not only is characterized by elevated blood glucose and blood lipid levels but also displays a protein metabolic disorder, which is primarily caused by the absolute or relative deficiency in insulin secretion [98]. Insulin can promote protein synthesis and inhibit protein decomposition [99], and increased insulin and insulin-like growth factor 1 (IGF1) levels in the serum can improve the protein metabolism (Figure 1). Compared with that in a normal group, protein catabolism in diabetic models was significantly ameliorated, while protein synthesis and the mRNA expression of the IR, IGF1, and IGF1 receptor (IGF1R) were markedly decreased [100].…”
Section: Protein Changes In Ad and Dmmentioning
confidence: 99%
“…The use of heamatological indices in establishing the harmful effects of xenobiotics has been reported [36]. Reduction of packed cell volume (aneamia) associated with diabetes mellitus has been attributed to increase in nonenzymatic glycosylation of RBC membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of ZA was performed according to the method described by Ren et al (2017) and its HPLC chromatogram is shown in…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…Z. bungeanum, a cooking sauce, is one of the eight traditional condiments in China that involves a tingling sensation as part of the taste profile. The primary factor for tongue numbness in Z. bungeanum is Zanthoxylum alkylamides (ZA) which include α, γ, β-sanshool and their homologues with a hydroxy in the amino portion (Mei, 2012;Ren et al, 2017;Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation